Impact of Increased Travel Speed of a Transportation Set on the Dynamic Parameters of a Mine Suspended Monorail - Kamil Szewerda; Jarosław Tokarczyk; Andrzej Wieczorek (Energies, 2021)
The method of increasing the efficiency of using one of the most common means of auxiliary transport in underground coal mines—suspended monorails—is presented. Increase of velocity is one of the key parameters to improve the efficiency and economical effect related with the underground auxiliary transport. On the other hand, increasing the velocity results in bigger value of force acting on the suspended monorail route and its suspensions. The most important issue during increasing the velocity is ensuring the required safety for the passengers and not overloading the infrastructure. In order to analyze how increasing velocity influences the level of loads of the route suspension and the steel arch loads, the computational model of suspended monorail was developed. The computational model included both the physical part (embedded in the program environment based on the Multi-Body System method) and the components of the monorail control system. Two independent software environments were cooperating with each other through the so-called co-simulation. This model was validated on the base of results obtained on the test stand. Then, the numerical simulations of emergency braking with different values of velocity were conducted, which was not possible with the use of physical objects. The presented study can be used by the suspended monorail’s producers during the designing process, and leads to increase the safety on underground transportation routes.